2014
DOI: 10.1111/php.12295
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Erythematic Radiation Dose Received by Golfers in Winter, in Valencia

Abstract: This article analyzes Ultraviolet Erythematic Radiation (UVER) dose received by several golf players in winter in Valencia. Playing golf involves spending several hours outdoors because of the length of golf matches and training. Moreover, in Valencia there are many golf players coming from northern Europe, with a phototype very sensitive (I-II). For that reason, these people have an increasing risk while playing. This article shows that harmful effects coming from UVER radiation may occur not only in summer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…8–9 h) Rigel et al 2003 [ 63 ] Professional ski instructors, Vail, Colorado, USA Digital dosimeters Mean daily mean UVB exposure was 62.08 mJ/cm 2 (range 12–185 mJ/cm 2 ) (0.5–7.6 times MED for type II skin) Mean daily UVA exposure was 10.6 (range 0.5–28 J/cm 2 ) (0.55 of minimum melanogenic dose) Downs et al 2009 [ 62 ] Golfers, Queensland Australia during summer and winter months. 2 recreational golfers vs 2 office workers, assuming one 9-hole game/week; 2–2.5 h Calibrated polysulfone dosimeter Estimated annual exposure: SED of 817 and 839 for forearm and upper back, respectively Downs et al 2020 [ 64 ] Olympic mixed sports, dose calculation for athletes due to compete in Tokyo 2020 Events lasting 2 h or more had personal erythematic exposures in excess of 200 J/m 2 Gurrea Ysasi et al 2014 [ 70 ] Golfers, winter (January), Valencia, Spain Dosimeters: 1 on hat, 1 on wrist Mean daily UVER exposure: head 2.07 ± 0.80 SED, wrist 1.62 ± 0.77 SED. Mean exposure per hour was 0.44 SED for head and 0.34 SED for wrist Exposure limit 0.3 MED per 8 h [ 61 ] SED standard erythema dose, MED minimal erythema dose, UVER ultraviolet erythematic radiation a Standard erythema dose (SED) is used as a standardised measure of erythemogenic UV radiation.…”
Section: Resultsmentioning
confidence: 99%
“…8–9 h) Rigel et al 2003 [ 63 ] Professional ski instructors, Vail, Colorado, USA Digital dosimeters Mean daily mean UVB exposure was 62.08 mJ/cm 2 (range 12–185 mJ/cm 2 ) (0.5–7.6 times MED for type II skin) Mean daily UVA exposure was 10.6 (range 0.5–28 J/cm 2 ) (0.55 of minimum melanogenic dose) Downs et al 2009 [ 62 ] Golfers, Queensland Australia during summer and winter months. 2 recreational golfers vs 2 office workers, assuming one 9-hole game/week; 2–2.5 h Calibrated polysulfone dosimeter Estimated annual exposure: SED of 817 and 839 for forearm and upper back, respectively Downs et al 2020 [ 64 ] Olympic mixed sports, dose calculation for athletes due to compete in Tokyo 2020 Events lasting 2 h or more had personal erythematic exposures in excess of 200 J/m 2 Gurrea Ysasi et al 2014 [ 70 ] Golfers, winter (January), Valencia, Spain Dosimeters: 1 on hat, 1 on wrist Mean daily UVER exposure: head 2.07 ± 0.80 SED, wrist 1.62 ± 0.77 SED. Mean exposure per hour was 0.44 SED for head and 0.34 SED for wrist Exposure limit 0.3 MED per 8 h [ 61 ] SED standard erythema dose, MED minimal erythema dose, UVER ultraviolet erythematic radiation a Standard erythema dose (SED) is used as a standardised measure of erythemogenic UV radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Gurrea Ysasi et al . (*) equipped fair‐skinned volunteers with VioSpor badges at the wrist and at the top of the cap. It was shown that PE can exceed the individual MED of skin types I and II (2 SED) even in January.…”
Section: Chronological Overviewmentioning
confidence: 99%
“…Another clichéd sport is golf. Four studies have been undertaken (*, *, *, *, *), but ERTA on comparable or the same positions shows large variations. This may be caused by the surrounding vegetation or by weather conditions.…”
Section: Summary On Exposure Ratiosmentioning
confidence: 99%
“…8,9,[12][13][14][15][16][17] However, few published studies have focused on solar exposure received by outdoor athletes using dosimeters to objectively measure personal exposure to UVR. 6,[18][19][20][21][22][23][24][25] Personal dosimetry allows quantifying UVR received by the athlete during sport. These studies conducted with runners, cyclists, skiers, golfers, tennis players, hikers, triathletes and rowers, found personal sun exposure levels from 0.062 standard erythemal dose (SED) for marathon runners to more than 30 SED for triathletes during an Ironman.…”
Section: Introductionmentioning
confidence: 99%
“…These studies conducted with runners, cyclists, skiers, golfers, tennis players, hikers, triathletes and rowers, found personal sun exposure levels from 0.062 standard erythemal dose (SED) for marathon runners to more than 30 SED for triathletes during an Ironman. 6,[18][19][20][21][22][23][24][25] Of these studies, just two 23,24 have been conducted with athletes in water sports, one to triathletes (during swimming, cycling and running stages) 23 and one to rowers. 24 Downs et al carried out research on personal solar ultraviolet exposure, measured using polysulphone film dosimeters, to triathletes during competitive Sprint, Olympic and Ironman events in Australia and New Zealand.…”
Section: Introductionmentioning
confidence: 99%